Mapping School Proximity to Cigarette Advertisements and Cigarette Retailers in Kota Baru District Jambi City - Syukri, Muhammad; Halim, Rd. (GLOBAL HEALTH SCIENCE GROUP, 2023)
Jambi City has a high proportion of first-time smokers. There are no regulations governing the sale of cigarettes around schools. Studies mapping cigarette sales and advertisements have been conducted in Indonesia, but so far no similar studies have been conducted in Jambi City. This study aims to map the distribution of cigarette sellers and advertisements to schools in Kota Baru District, Jambi City. This study was conducted by recording data on the coordinates of schools and the coordinates of cigarette advertisement locations and cigarette retailers. Data was collected using the open-source application KoBoToolbox. Data analysis was conducted through 2 stages. The first was descriptive data analysis to create a cross-table of types of educational facilities with types of shops and types of advertisements. This analysis used the IBM SPSS 25.0 application. Second, mapping with the buffer method to draw the radius of schools with types of shops and types of advertisements. The radius distance in this study is 100 meters and 300 meters from the school point to the type of advertisement and type of retailers. The mapping used the help of the open-source application Quantum GIS 3.30.2. The results of this study found many shops selling cigarettes around the school radius of 100 meters and 300 meters, dominated by grocery stores. The results of this study also found that there are still advertisements posted around educational facilities within a radius of 100 meters and 300 meters, dominated by the types of advertisements in the form of banners and banners.